2016
DOI: 10.1177/0897190015585764
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Preferences for Communication of Pharmacist-Provided Medication Therapy Management in Community Pharmacy

Abstract: Survey respondents saw value in the MTM services offered by pharmacists. However, pharmacists should use the identified preferences and barriers to improve their currently utilized communication practices in hopes of increasing acceptance of recommendations. Ultimately, this may assist MTM providers in working collaboratively with patients' physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…[26][27] Various strategies for improving these relationships have been suggested such as the pharmacist being the initiator of relationships, building trust through provision of high quality patient care recommendations, providing education to physicians on the pharmacist's role, and utilizing facsimile while exploring other prescriber-preferred methods to communicate recommendations. [28][29][30] Similarly, prior work has found that referrals to community resources as part of MTM are uncommon 18 and that opportunities to enhance collaborations between community pharmacies and other community-based organizations is evident. 31 The use of scripted language for introducing/explaining MTM also is addressed by one of the items in the facilitators scale.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27] Various strategies for improving these relationships have been suggested such as the pharmacist being the initiator of relationships, building trust through provision of high quality patient care recommendations, providing education to physicians on the pharmacist's role, and utilizing facsimile while exploring other prescriber-preferred methods to communicate recommendations. [28][29][30] Similarly, prior work has found that referrals to community resources as part of MTM are uncommon 18 and that opportunities to enhance collaborations between community pharmacies and other community-based organizations is evident. 31 The use of scripted language for introducing/explaining MTM also is addressed by one of the items in the facilitators scale.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists have encountered barriers to communication and mixed responses to the consulting pharmacist recommendations for medication therapy management. 38 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…The acceptance rate for medication therapy management (MTM) ranges from 30% to 60% [18,19,20,21]. Prescriber resistance has been reported as one of the biggest barriers to providing MTM services [22,23].…”
Section: Discussionmentioning
confidence: 99%